2018
DOI: 10.14419/ijet.v7i3.12.17875
|View full text |Cite
|
Sign up to set email alerts
|

Transient Stability Enhancement of DFIG based Offshore Wind Farm Connected to a Power System Network using STATCOM

Abstract: This paper presents the transient stability enhance of DFIG-based offshore wind farm connected power system network using STATCOM. The studied system is simulated in MATLAB/Simulink platform for study the effect of transient disturbances like, three phases to ground fault, sudden load change, voltage sag & swell. A fully aggregate model of wind DFIG is used for simulation study of system. The DFIG based wind generator, more sensitive to the grid faults than other wind generators. During transient disturban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It is one of the most prominent dietary antioxidants. This is mainly because of the reactivity of phenolic compounds with free radical species to form phenoxy radicals, which are considerably less reactive . It has been shown to exert beneficial health effects in various diseases, including osteoporosis, cancer, pulmonary and cardiovascular diseases .…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most prominent dietary antioxidants. This is mainly because of the reactivity of phenolic compounds with free radical species to form phenoxy radicals, which are considerably less reactive . It has been shown to exert beneficial health effects in various diseases, including osteoporosis, cancer, pulmonary and cardiovascular diseases .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that GSHP has been increasingly used for building heating and cooling in recent years at an annual rate of increase of 10% to 12%. Several studies have been conducted to examine the industrial sector in Jordan [5][6][7][8][9][10][11][12], concentrating on the effectiveness of each renewable energy source. A simulation of the different structures of the SAGSHP system for residential construction was conducted [13].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the MATLAB/SIMULINK simulations revealed the effectiveness of the control strategies. Similarly, [13] proposed a system that used STATCOM to achieve the reactive power obligation in order to stabilize the wind farm [13].…”
Section: Introductionmentioning
confidence: 99%